The Strategy of Realizing Sharia Based School Cooperative in Tasikmalaya City, Indonesia - Asep Suryanto (International Journal of Nusantara Islam, 2017)
The objectives of this research: 1) what factors become a problem so that school cooperative still not become sharia based school cooperative? 2) How is the strategy to realize sharia cooperative in school? This research used a qualitative approach, i.e., Analytic Network Process (ANP). In applying the ANP method, the researcher does the following: 1) structuring the hierarchical complexity into the homogeneous clusters of the factors, 2) performing the measurements into the ratio scale at all the lowest levels of the hierarchy/ network, 3) synthesizing. Data used in this research is primary data collected from questionnaires and in depth interview with experts, the policy holder, students, and teacher coach. The results of the research show that 1) The factors that become the problem of difficulties in realizing sharia-based school cooperatives are less student participation, limited capital and infrastructure, knowledge of sharia co-operatives that are less good than students and teachers, and lack of coaching from the local cooperative office. 2) There are two strategies as a solution, i.e., an internal strategy which is the policy of school leadership to support the establishment of sharia-based school cooperatives; And external strategies that should be carried out by the government to support and develop sharia cooperatives including sharia-based school cooperatives.